Polarizing plate, thermally molded article, and method
By using a polyethylene glycol (PVA) polarizing film with an amorphous quantity and an appropriate amount of boric acid, combined with specific stretching and cross -linking processing processes to form a polarizing board with high polarizing performance The problem of cracking has achieved the polarizing performance of the polarizing performance after the large deformation heat.
Patent Information
- Application Number
- CN202380047154.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-28
- Filing Date
- 2023-06-27
- Publication Date
- 2025-01-28
AI Technical Summary
Existing polarizing plates are prone to cracks during the thermoforming process, resulting in a reduced polarization performance, and the light-shielding function in optical applications such as sunglasses and the effect of preventing mapping in vehicle-mounted applications.
Polyvinyl alcohol (PVA) polarizer containing high -oriented ullen volume and appropriate amount of boric acid is used, which is greater than 20 μm. It forms a polarizer with high polarizing performance through specific stretching and cross -linking processing processes. The polarized board uses a spherical depression mold with a curvature radius at the heat forming, and is heated and vacuum under the vacuum conditions of 107 ° C.
The polarization board is achieved in the process of large deformation heat and does not produce cracks, maintains sufficient polarizing performance, and is suitable for polarizing boards with high design of highly designed sunglasses and instrument panels.
Smart Images

Figure BDA0005187382460000261 
Figure HDA0005187382480000011 
Figure HDA0005187382480000012
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing plate, a thermoformed body, and a method for producing the thermoformed body. Background Art
[0002] The mainstream of polarizing film is iodine-based pigment (I 3- ,I 5- A film obtained by adsorbing dichroic pigments such as dichroic organic dyes on a substrate (a stretched film uniaxially stretched to orient it) formed by uniaxially stretching a polyvinyl alcohol (hereinafter sometimes "polyvinyl alcohol" is abbreviated as "PVA") film. This polarizing film is produced by uniaxially stretching a PVA film that contains a dichroic pigment in advance, or by adsorbing the dichroic pigment while uniaxially stretching the PVA film, or by adsorbing the dichroic pigment after uniaxially stretching the PVA film. A polarizing plate obtained by attaching a protective film such as a triacetyl cellulose (TAC) film, an acrylic film, or a polyester film to both sides or one side of the obtained polarizing film has light-transmitting and light-shielding functions, and is a basic component of a liquid crystal display (LCD) together with liquid crystals that change the polarization state of light.
[0003] In addition, polarizing plates are used for optical purposes such as sunglasses, goggles, and glasses by utilizing light transmission and light shielding functions. In these applications, it is necessary to process the polarizing plates into lens shapes such as curved surfaces. As a molding method for polarizing plates for these applications, thermoforming is generally used.
[0004] Furthermore, in recent years, as one of the vehicle-mounted uses, the introduction of polarizing plates on the dashboard of a car has been studied. It has been pointed out that the reflection of external light on the dashboard is sometimes mapped onto the front windshield, which results in reduced visibility for the driver. As a solution to this problem, it has been proposed that the function of the polarizing plate to absorb and shield light in a specific direction is utilized, and a polarizing plate is arranged on the dashboard to suppress the reflection of external light on the dashboard and prevent mapping (Patent Document 1). In this use, if the polarizing plate does not have a shape that fits closely to the dashboard, the effect of preventing mapping cannot be fully exerted, and therefore, a polarizing plate that can be thermoformed to match the shape of the dashboard is sought.
[0005] However, since the polarizing plate requires high polarization performance, the PVA needs to be sufficiently oriented, and therefore the elongation in the stretching direction is small. If deformation is applied in the stretching direction during thermoforming, cracks may occur in a direction perpendicular to the stretching direction.
[0006] The following method is proposed: as a polarizing film having elasticity that can follow the stretching of the body and clothing, a polyvinyl alcohol-based resin film containing a halide is used, wherein the polyvinyl alcohol-based resin film has a deformation amount of 10% or more when stretched at a load change rate of 98.0 mN / min along the absorption axis at room temperature, and a shrinkage rate of 5% or less in the absorption axis direction when heated at 85° C. for 120 minutes (Patent Document 2). However, Patent Document 2 does not describe a polarizing film suitable for high-temperature thermoforming.
[0007] In addition, in vehicle applications, as a means of preventing cracks from occurring in a direction perpendicular to the stretching direction, the following method has been proposed: a raw material film is stretched in one direction to impart polarization characteristics, while being shaped into the surface shape of an object component, and is simultaneously attached to the surface of the object component, and then the raw material film is dried (Patent Document 3). However, durability is required in vehicle applications, and therefore, a protective film needs to be attached to the polarizing layer attached to the surface of the object component, and it is not easy to efficiently attach a protective film to the polarizing film formed by this method.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2004-130916
[0011] Patent Document 2: International Publication No. 2020 / 255779
[0012] Patent Document 3: Japanese Patent Application Publication No. 2019-51874 Summary of the invention
[0013] Problems to be solved by the invention
[0014] In recent years, polarizing plates that have been thermoformed with large deformations are increasingly being used in optical applications such as sunglasses with high design. In addition, in vehicle-mounted applications, in order to improve design, curved instrument panels with even greater deformations are increasing. However, conventional polarizing plates have the problem of being prone to cracking during the thermoforming process. In addition, when thermoforming a polarizing plate, there is also a portion that is deformed in a direction perpendicular to the stretching direction of the polarizing plate. Therefore, sometimes the polarization performance of the thermoformed body of this portion is reduced, and the shading function in optical applications such as sunglasses and the effect of preventing reflection in vehicle-mounted applications cannot be fully exerted. Therefore, a polarizing plate that takes into account both polarization performance and thermoformability is sought.
[0015] That is, an object of the present invention is to provide a polarizing plate having sufficient polarization performance and being less likely to crack even when the amount of deformation during thermoforming is large, a thermoformed article obtained by thermoforming such a polarizing plate, and a method for producing the thermoformed article.
[0016] Means used to solve problems
[0017] The present inventors have conducted intensive studies to solve the above problems and have completed the present invention. That is, the present invention is the following [1] to [9].
[0018] [1] A polarizing plate comprising a polarizing film containing polyvinyl alcohol as a main component, wherein the thickness of the polarizing film is greater than 20 μm and the amount of highly oriented amorphous particles in the polarizing film is 10.0 to 18.0%.
[0019] [2] The polarizing plate according to [1], wherein the polarizing film has a boric acid content of 5 to 30% by mass.
[0020] [3] The polarizing plate according to [1] or [2], wherein the amount of highly oriented PVA-boric acid aggregated structures in the polarizing film is 4.3% or less.
[0021] [4] The polarizing plate according to any one of [1] to [3], wherein the polarizing film contains a dichroic organic dye.
[0022] [5] A polarizing plate according to any one of [1] to [4], wherein the crack rate is 0 to 40% when heat vacuum forming is performed using a mold having a spherical recess with a curvature radius of 5.2 cm and a depth of 3.5 cm at a temperature of 107°C and a vacuum degree of 0.01 MPa.
[0023] [6] A thermoformed article obtained by thermoforming the polarizing plate according to any one of [1] to [5].
[0024] [7] The thermoformed article according to [6], wherein the maximum elongation is 35% or less.
[0025] [8] The thermoformed article according to [6] or [7], which has a polarization degree of 80 to 99.7%.
[0026] [9] A method for producing a thermoformed article, comprising the step of thermoforming the polarizing plate according to any one of [1] to [5] at 105°C to 110°C.
[0027] Effects of the Invention
[0028] By using the polarizing plate of the present invention, a thermoformed article having sufficient polarization performance and little or no cracking even when the deformation is large can be obtained. In addition, by using the method for producing a thermoformed article of the present invention, the above-mentioned excellent thermoformed article is provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1This is a schematic diagram of measured data obtained by an X-ray curve with respect to a polarizing film.
[0030] Figure 2 is based on Figure 1 Schematic diagram of the baseline correction drawn in.
[0031] Figure 3 This is a schematic diagram of fitting the amorphous part using a Gaussian function.
[0032] Figure 4 This is a schematic diagram when the crystal part is fitted using a Gaussian function.
[0033] Figure 5 This is a graph showing a baseline straight line drawn from the I(2θ) curve.
[0034] Figure 6 The baseline-corrected I(2θ) curve is separated into "PVA amorphous", "PVA crystalline" and "PVA-boric acid aggregate structure".
[0035] Figure 7 This is a graph in which the integrated intensity values (A) of "PVA amorphous", "PVA crystalline", and "PVA-boric acid aggregate structure" obtained by waveform separation analysis are plotted against azimuth.
[0036] Figure 8 This is a diagram in which the integrated intensity value (A) is separated into an oriented component and a non-oriented component.
[0037] Fig. 9 It is a diagram for explaining the maximum deformation length A and the diameter B of the forming die. DETAILED DESCRIPTION
[0038] The present invention is described in detail below. It should be noted that in this specification, the upper limit and lower limit of the numerical range (the content of each component, the value calculated based on each component, and each physical property, etc.) can be appropriately combined. When there is a record of the numerical range of "XX to YY" in this specification, it means "above XX and below YY". In addition, PVA film refers to a film that contains PVA and is usually not stretched, and polarizing film refers to a uniaxially stretched PVA film containing a dichroic pigment.
[0039] [PVA film]
[0040] The polarizing plate of the present invention includes a polarizing film, which is a uniaxially stretched PVA film containing a dichroic pigment. As the raw material of the PVA film, that is, PVA, a PVA obtained by saponifying a polyvinyl ester obtained by polymerizing one or more of vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl pivalate, vinyl versatate, vinyl laurate, vinyl stearate, vinyl benzoate, and isopropenyl acetate can be used. Among the above-mentioned vinyl esters, from the viewpoints of ease of manufacture, ease of acquisition, cost, etc. of PVA, a compound having a vinyloxycarbonyl group in the molecule is preferred, and vinyl acetate is more preferred.
[0041] The polyvinyl ester is preferably a substance obtained by using only one or more vinyl esters as monomers, and more preferably a substance obtained by using only one vinyl ester as a monomer. Among them, as long as the effect of the present invention is not significantly impaired, it can be a copolymer of one or more vinyl esters and other monomers copolymerizable therewith.
[0042] Examples of the other monomers copolymerizable with the vinyl ester include α-olefins having 2 to 30 carbon atoms, such as ethylene, propylene, 1-butene, and isobutylene; (meth)acrylic acid or its salts; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; (meth)acrylamide; N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, diacetone (meth)acrylamide, (meth)acrylamide propanesulfonic acid or its salts, (meth)acrylic acid esters such as propanesulfonic acid ester and propanesulfonic acid ester; (Meth)acrylamide derivatives such as (methyl)acrylamide propyl dimethylamine or its salt, N-hydroxymethyl (meth)acrylamide or its derivatives; N-vinylamides such as N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; vinyl cyanide such as (meth)acrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or its salt, ester or anhydride; itaconic acid or its salt, ester or anhydride; vinyl silyl compounds such as vinyltrimethoxysilane; unsaturated sulfonic acid or its salt, etc. The above-mentioned polyvinyl ester may have a structural unit derived from one or more monomers among the above-mentioned other monomers.
[0043] The proportion of the structural units derived from the other monomers in the polyvinyl ester is preferably 15 mol% or less, more preferably 10 mol% or less, and further preferably 5 mol% or less, based on the number of moles of all structural units constituting the polyvinyl ester.
[0044] As PVA, PVA that has not been graft copolymerized can be preferably used. Among them, PVA can be modified using one or more graft copolymerizable monomers as long as the effect of the present invention is not significantly impaired. The graft copolymerization can be carried out on at least one of polyvinyl ester and PVA obtained by saponifying it. Examples of the above-mentioned graft copolymerizable monomers include unsaturated carboxylic acids or their derivatives; unsaturated sulfonic acids or their derivatives; α-olefins having 2 to 30 carbon atoms, etc. The proportion of the structural units derived from the graft copolymerizable monomers in the polyvinyl ester or PVA is preferably 5 mol% or less based on the molar number of all structural units constituting the polyvinyl ester or PVA.
[0045] A part of the hydroxyl groups in the PVA may be cross-linked or not. In addition, a part of the hydroxyl groups in the PVA may react with aldehyde compounds such as acetaldehyde and butyraldehyde to form an acetal structure or may not react with these compounds to form an acetal structure.
[0046] The degree of polymerization of PVA is not particularly limited, but is preferably 1,000 or more. By setting the degree of polymerization of PVA to be 1,000 or more, the polarization performance of the resulting polarizing film can be further improved. If the degree of polymerization of PVA is too high, there is a tendency for the manufacturing cost of PVA to increase and the process quality during film making to be poor. The degree of polymerization of PVA is more preferably in the range of 1,000 to 10,000, further preferably in the range of 1,500 to 8,000, and particularly preferably in the range of 1,800 to 4,000. The degree of polymerization of PVA is the viscosity average degree of polymerization measured by the method described in JIS-K6726-1994.
[0047] From the aspect that the durability of the obtained polarizing film becomes good, the saponification degree of PVA is preferably 95 mol% or more, more preferably 98 mol% or more, further preferably 99 mol% or more, and particularly preferably 99.3 mol% or more. The upper limit of the saponification degree of PVA can be 100 mol%. The saponification degree of PVA is a value measured by the method described in JIS-K6726-1994.
[0048] The PVA film used in the polarizing plate of the present invention will be described.
[0049] The PVA film is a film with PVA as the main component. The main component refers to the component with the largest content based on mass. The PVA content in the PVA film is preferably in the range of 50 to 100 mass %, more preferably in the range of 80 to 100 mass %, and further preferably in the range of 85 to 100 mass %.
[0050] The PVA film may contain a plasticizer. By making the PVA film contain a plasticizer, it is possible to achieve an improvement in the handling and stretchability of the PVA film. As a plasticizer, it is preferred to use a polyol, and as a specific example, ethylene glycol, glycerol, propylene glycol, diethylene glycol, diglycerol, triethylene glycol, tetraethylene glycol, trimethylolpropane, etc. can be listed. The PVA film may contain one or more of these plasticizers. Among these, glycerol is preferably used from the aspect that the stretchability of the PVA film becomes better.
[0051] The content of the plasticizer in the PVA film is preferably less than 15 parts by mass relative to 100 parts by mass of PVA, more preferably less than 10 parts by mass, and further preferably less than 5 parts by mass. By making the content of the plasticizer in the PVA film less than 15 parts by mass relative to 100 parts by mass of PVA, it is possible to suppress the plasticizer from oozing out of the surface of the PVA film, and it is possible to suppress the handling property of the PVA film from decreasing. The lower limit of the content of the plasticizer in the PVA film can be 0 parts by mass, or 1 part by mass or 5 parts by mass relative to 100 parts by mass of PVA.
[0052] The PVA film preferably contains a surfactant. By containing a surfactant, it is expected that the uneven thickness of the film when the PVA film is produced using a film-making stock solution containing PVA can be suppressed, the film-making property can be improved by easily peeling the PVA film from a metal roll or a belt after film-making, and the anti-blocking effect of the obtained films can be achieved. The type of surfactant contained in the PVA film is not particularly limited, and from the viewpoint of peelability from a metal roll or a belt, an anionic surfactant or a nonionic surfactant is preferably used, and a nonionic surfactant is particularly preferably used.
[0053] Preferred anionic surfactants include, for example, carboxylic acid type surfactants such as potassium laurate; sulfate ester type surfactants such as octyl sulfate; and sulfonic acid type surfactants such as dodecylbenzenesulfonate.
[0054] As the nonionic surfactant, preferred are, for example, alkyl ether types such as polyoxyethylene oleyl ether; alkyl phenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkyl amine types such as polyoxyethylene lauryl amino ether; alkyl amide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; allyl phenyl ether types such as polyoxyalkylene allyl phenyl ether, etc.
[0055] These surfactants can be used alone or in combination of two or more.
[0056] The content of the surfactant in the PVA film is preferably in the range of 0.01 to 0.5 parts by mass, and more preferably in the range of 0.02 to 0.3 parts by mass, relative to 100 parts by mass of PVA. By making the content of the surfactant 0.01 parts by mass or more relative to 100 parts by mass of PVA, the occurrence of defects can be suppressed, and the peeling property from the metal roll can be improved. On the other hand, by making the content of the surfactant 0.5 parts by mass or less relative to 100 parts by mass of PVA, the adhesion of the film caused by the seepage of the surfactant can be suppressed, and stable handling can be achieved.
[0057] The PVA film may be composed of only PVA, and may contain at least one of a plasticizer and a surfactant. The PVA film may further contain other ingredients such as an antioxidant, an antifreeze agent, a pH adjuster, a shielding agent, an anti-coloring agent, and an oil agent as required.
[0058] The PVA film used in the manufacture of the polarizing plate of the present invention is not particularly limited. In order to manufacture a polarizing plate with sufficient polarization performance, the crystallinity is preferably 31% or more. In addition, from the perspective of easily obtaining a polarizing plate with few cracks during thermoforming, the crystallinity is preferably 35% or less. It should be noted that the crystallinity can be obtained by using the measurement method described below. The crystallinity of the PVA film can be adjusted according to the composition of the film-making stock solution during film making, the temperature conditions and atmosphere during drying and heat treatment, etc. The crystallinity of the PVA film can also be controlled by adjusting the type and content of the plasticizer.
[0059] [PVA film production method]
[0060] As the film-making method of PVA film, for example, a film-making method using a film-making stock solution comprising PVA, a film-making method of casting, an extrusion film-making method, a wet film-making method, a gel film-making method, etc. can be listed. These film-making methods can only adopt one kind, or two or more kinds can be used in combination. Among these film-making methods, from the aspect of being able to obtain a PVA film with uniform thickness and width and good physical properties, preferably a film-making method of casting or an extrusion film-making method. Drying rollers and heat treatment rollers can be used as needed to dry and heat-treat the PVA film.
[0061] The preparation of the film-forming stock solution is usually carried out by dissolving PVA in a liquid solvent. Examples of the liquid medium include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, and diethylenetriamine, and one or more of these can be used. Among them, water is preferred from the viewpoint of small burden on the environment and recyclability.
[0062] The volatility of the film-forming stock solution (the proportion of volatile components such as liquid medium that are removed by volatilization and evaporation during film-forming) varies depending on the film-forming method, film-forming conditions, etc., and is preferably in the range of 50 to 95% by mass, more preferably in the range of 55 to 90% by mass, and further preferably in the range of 60 to 85% by mass. By making the volatility of the film-forming stock solution 50% or more by mass, the viscosity of the film-forming stock solution will not be too high, and filtration and degassing during the preparation of the film-forming stock solution will be smoothly performed, making it easy to manufacture a PVA film with few foreign matter and defects. On the other hand, by making the volatility of the film-forming stock solution 95% or less by mass, the concentration of the film-forming stock solution will not become too low, and it is easy to industrially manufacture PVA films.
[0063] The temperature during drying of the PVA film is not particularly limited, but is preferably in the range of 80 to 120° C., more preferably in the range of 83 to 105° C., and even more preferably in the range of 85 to 95° C. from the viewpoint of film drying uniformity, productivity, etc.
[0064] The PVA film is preferably subjected to heat treatment for reasons such as improving productivity in the manufacturing process of the polarizing film. The heat treatment temperature is preferably 90°C or higher, more preferably 100°C or higher, and further preferably 110°C or higher. In addition, from the viewpoint of improving the stretchability of the obtained PVA film, the surface temperature of the heat treatment roller is preferably 150°C or lower, more preferably 140°C or lower, and further preferably 130°C or lower.
[0065] The thickness of the PVA film is not particularly limited, but is preferably 75 μm or more, more preferably 80 μm or more, and further preferably 85 μm or more. By making the thickness of the PVA film 75 μm or more, it is not easy to break during stretching, and the polarizing film can be stably manufactured. On the other hand, from the perspective of being able to manufacture the polarizing film more smoothly, the thickness is preferably 160 μm or less, and more preferably 150 μm or less. It should be noted that the "thickness" of the PVA film and the polarizing film described later refers to the average value (average thickness) of the measured values at any 5 locations.
[0066] The shape of the PVA film is not particularly limited. From the perspective of being able to continuously manufacture polarizing films with good productivity, it is preferably a long strip film. The length of the long strip film is not particularly limited, and can be appropriately set according to the purpose of the manufactured polarizing film, for example, it can be set in the range of 5 to 20,000 m. The width of the long strip film is not particularly limited, for example, it can be set to 50 cm or more. From the perspective of seeking wide-width polarizing films in recent years, it is preferably 1 m or more, more preferably 2 m or more, and further preferably 4 m or more. The upper limit of the width of the long strip film is not particularly limited. If the width is too wide, it tends to be difficult to stretch uniformly. Therefore, the width of the PVA film is preferably 7 m or less.
[0067] [Polarizing film]
[0068] Next, a polarizing film obtained by using the PVA film will be described.
[0069] The polarizing film contains PVA as a main component. The content of PVA in the polarizing film is preferably in the range of 50 to 99 mass %, more preferably in the range of 60 to 90 mass %, and further preferably in the range of 70 to 85 mass %. The polarizing film may be a single-layer film containing PVA as a main component.
[0070] Cracks generated when the polarizing plate is thermoformed can significantly affect the solid structure of the polarizing film.
[0071] The solid structure of the polarizing film can be analyzed by wide-angle X-ray diffraction (WAXD) measurement, and can be divided into three components: "PVA crystal", "PVA amorphous" and "PVA-boric acid aggregate structure" for quantification. Here, "PVA crystal" refers to a crystalline structure containing PVA chains in a crystalline state, and "PVA amorphous" refers to an amorphous structure containing PVA chains that are not in a crystalline state. "PVA amorphous" may contain an amorphous structure other than PVA chains. That is, "PVA amorphous" can be simply replaced by "amorphous" (the part that is not in a crystalline state: amorphous structure). In addition, "PVA-boric acid aggregate structure" refers to a structure derived from a peak that is known to appear in the X-ray curve when boric acid is contained in the polarizing film, and it can be considered that the peak is a diffraction signal derived from a structure formed by the interaction between PVA and boric acid.
[0072] In addition, the wide-angle X-ray diffraction (WAXD) measurement of the polarizing film used in the present invention is a well-known method, and is described in, for example, International Publication No. 2017 / 138551.
[0073] These three components can be further divided into three components, namely, non-oriented component, low-oriented component and high-oriented component, respectively, with respect to the stretching direction of the polarizing film, and can be divided into nine components in total. In this way, the ratio (%) of each component when the nine components are set as 100% can be calculated. It should be noted that the detailed WAXD measurement and analysis method will be described in detail later.
[0074] Highly oriented amorphous refers to the highly oriented component in "PVA amorphous". Highly oriented amorphous is a structure in which the PVA chains in the amorphous state are highly oriented. According to the WAXD measurement and its analysis method described later, highly oriented amorphous can be defined as a structure in which the PVA chains in the amorphous state are arranged within a range of ±10° relative to the stretching direction. It can be considered that the highly oriented amorphous is a part that is not easily deformed when the polarizing plate is thermoformed. In other words, it can be inferred that the less the amount of highly oriented amorphous in the polarizing film contained in the polarizing plate, the greater the amount of elongation in the stretching direction of the polarizing film, and the easier it is to thermoform the polarizing plate. The amount of highly oriented amorphous refers to the ratio (%) of the amount of highly oriented amorphous (highly oriented component in PVA amorphous) to the total amount of PVA crystals, PVA amorphous and PVA-boric acid aggregated structures.
[0075] The amount of highly oriented amorphous in the polarizing film contained in the polarizing plate of the present invention is 10.0 to 18.0%. When the amount of highly oriented amorphous is less than 10.0%, the polarization performance may be significantly reduced. The amount of highly oriented amorphous is preferably 11.0% or more, more preferably 12.0% or more, and further preferably 14.0% or more. On the other hand, when the amount of highly oriented amorphous exceeds 18.0%, cracks are likely to occur during thermoforming. The amount of highly oriented amorphous is preferably 17.0% or less, more preferably 16.0% or less.
[0076] Highly oriented PVA-boric acid aggregate structure refers to the highly oriented component in the "PVA-boric acid aggregate structure". In the present invention, the amount of highly oriented PVA-boric acid aggregate structure of the polarizing film is not particularly limited. If the cross-linked structure of PVA and boric acid increases, the polarizing film becomes harder, so it is preferably 4.3% or less. The lower limit of the amount of highly oriented PVA-boric acid aggregate structure can be 0%, or it can be 1.0%, 2.0% or 3.0%. According to the WAXD measurement and its analysis method described later, the highly oriented PVA-boric acid aggregate structure can be defined as a structure in which the PVA chains in the state of interacting with boric acid (that is, the PVA chains in the PVA-boric acid aggregate structure) are arranged within a range of ±10° relative to the stretching direction. The amount of highly oriented PVA-boric acid aggregate structure refers to: the ratio (%) of the amount of highly oriented PVA-boric acid aggregate structure (the highly oriented component in the PVA-boric acid aggregate structure) to the total amount of PVA crystals, PVA amorphous and PVA-boric acid aggregate structures.
[0077] The thickness of the polarizing film included in the polarizing plate of the present invention is greater than 20 μm. When the thickness of the polarizing film is less than 20 μm, it is easy to be strongly affected by the uneven film thickness or the proportion of the outer skin layer where stress is easily concentrated during stretching is likely to increase, so cracks may be easily generated during thermoforming. The thickness of the polarizing film is preferably greater than 21 μm, more preferably greater than 30 μm, and further preferably greater than 38 μm. On the other hand, the upper limit of the thickness of the polarizing film is not particularly limited. From the perspective of suppressing excessive rigidity and further improving thermoformability, it is preferably less than 45 μm, and more preferably less than 40 μm.
[0078] The amount of highly oriented amorphous in the polarizing film can be controlled by adjusting the degree of polymerization of PVA, the degree of saponification, the type and content of plasticizer, the drying temperature when manufacturing the PVA film, the boric acid content in the polarizing film, or the stretching temperature and stretching ratio in the stretching process when manufacturing the polarizing film described later. For example, if the content of plasticizer is increased, the amount of highly oriented amorphous tends to decrease. In addition, if the stretching temperature in the stretching process when manufacturing the polarizing film is increased or the stretching ratio is reduced, the amount of highly oriented amorphous tends to decrease. The amount of highly oriented PVA-boric acid aggregated structure in the polarizing film can also be controlled by adjusting any one or more of the above-mentioned factors. For example, if the boric acid content is reduced or the stretching ratio is reduced, the amount of highly oriented PVA-boric acid aggregated structure tends to decrease.
[0079] In the present invention, the polarizing film preferably contains a boron compound as a crosslinking agent. By containing a boron compound, a crosslinking structure can be constructed, and durability can be exerted in a hot and humid environment. Examples of the boron compound include boric acid, borates such as borax, and the like. These boron compounds can be used alone or in combination of multiple types. Among these boron compounds, boric acid is preferred from the viewpoint of improving durability in a hot and humid environment.
[0080] The boric acid content in the polarizing film is preferably 5 to 30% by mass relative to the mass of the polarizing film. By making the boric acid content 5% by mass or more, the durability in a hot and humid environment is sufficiently improved. The boric acid content in the polarizing film is more preferably 10% by mass or more, and particularly preferably 18% by mass or more. On the other hand, by making the boric acid content 30% by mass or less, the generation of cracks during thermoforming can be fully suppressed. The boric acid content in the polarizing film is more preferably 25% by mass or less.
[0081] The coloring agent of the polarizing film can use a dichroic pigment. As the dichroic pigment, iodine-based pigments, dichroic organic dyes, etc. can be listed. From the perspective of the heat resistance of the polarizing plate and the thermoformed body formed therefrom, dichroic organic dyes are particularly preferred. Specific examples of dichroic organic dyes are described below.
[0082] The polarizing film used in the present invention preferably does not contain halides. This is because halides can cause degradation of the polarizing plate during thermoforming. The content of halogen compounds in the polarizing film is preferably 1% by mass or less, more preferably 0.1% by mass or less, and particularly preferably 0.001% by mass or less.
[0083] [Polarizing film manufacturing method]
[0084] The method for producing the polarizing film included in the polarizing plate of the present invention is not necessarily limited, and any known method may be adopted. As a suitable method, the following method can be exemplified.
[0085] As a method for manufacturing the polarizing film of the present invention, the following method is preferred: after previously undergoing a treatment step for swelling the PVA film (hereinafter sometimes referred to as a "swelling step"), on the basis of a treatment step for dyeing the PVA film (hereinafter sometimes referred to as a "dyeing step") and a treatment step for stretching the PVA film (hereinafter sometimes referred to as a "stretching step"), a treatment step for crosslinking the PVA film using a crosslinking agent (hereinafter sometimes referred to as a "crosslinking step") is performed. The order of the dyeing step, the stretching step, and the crosslinking step is not limited, and it is preferred that the dyeing step, the crosslinking step, and the stretching step are performed in sequence after the swelling step.
[0086] Hereinafter, each step will be described in detail.
[0087] The swelling treatment in the swelling process can be performed by immersing the PVA film in water. The temperature of the water when immersed in water is preferably in the range of 20 to 55°C, more preferably in the range of 22 to 52°C, and further preferably in the range of 25 to 50°C. In addition, the time of immersion in water is, for example, preferably in the range of 0.1 to 5 minutes, more preferably in the range of 0.5 to 3 minutes. It should be noted that the water used for immersion in water is not limited to pure water, and can be an aqueous solution in which various components are dissolved, or a mixture of water and an aqueous medium.
[0088] The dyeing process in the dyeing step can be any order before the stretching process, while the stretching process and after the stretching process, preferably before the stretching process. The dyeing can be carried out using a dichroic pigment. As mentioned above, as the dichroic pigment, iodine-based pigments, dichroic organic dyes etc. can be listed.
[0089] Examples of the iodine-based pigment include: 3- ,I 5- Etc. These iodine-based pigments can be obtained, for example, by contacting iodine (I2) with potassium iodide. Therefore, for example, the PVA film can be dyed by immersing it in a solution (especially an aqueous solution) containing iodine-potassium iodide as a dyeing bath.
[0090] As the above-mentioned dichroic organic dye, for example, direct black 17, 19, 154; direct brown 44, 106, 195, 210, 223; direct red 2, 23, 28, 31, 37, 39, 79, 81, 240, 242, 247; direct blue 1, 15, 22, 78, 90, 98, 151, 168, 202, 236, 249, 270; direct violet 9, 12, 51, 98; direct green 1, 85; direct yellow 8, 12, 44, 86, 87; direct orange 26, 39, 106, 107, etc. These can be used in combination of two or more, and the mixing ratio is not particularly limited, and the mixing amount can be set arbitrarily. Therefore, by combining the above-mentioned dichroic organic dyes, the hue can be made dark gray.
[0091] The concentration of the dichroic dye in the aqueous solution containing the dichroic dye in the dyeing bath can be appropriately set according to the type of the dichroic dye, etc. For example, the concentration of the dichroic organic dye is preferably in the range of 0.001 to 0.3 mass %. In addition, the temperature of the dyeing bath is preferably set to 20 to 55° C., and particularly preferably set to 30 to 50° C.
[0092] The cross-linking treatment in the cross-linking process is a treatment in which the PVA film is immersed in an aqueous solution containing a cross-linking agent. If the cross-linking treatment is performed, a cross-linked structure is introduced into the PVA film, which can improve the heat resistance of the polarizing film. From this point of view, the cross-linking treatment is preferably performed after the dyeing treatment. As the cross-linking agent, one or more boron compounds such as borate such as boric acid and borax can be used. The concentration of the cross-linking agent in the aqueous solution containing the cross-linking agent is preferably in the range of 1 to 15% by mass, and more preferably in the range of 1.5 to 7% by mass. The aqueous solution containing the cross-linking agent may contain an auxiliary agent such as potassium iodide. The temperature of the aqueous solution containing the cross-linking agent is preferably in the range of 20 to 50°C, and more preferably in the range of 25 to 45°C.
[0093] The stretching treatment in the stretching process can be performed by either a wet stretching method or a dry stretching method. In the wet stretching method, uniaxial stretching can be performed in an aqueous solution containing boric acid. In addition, uniaxial stretching can be performed in the above-mentioned swelling bath, dyeing bath, and fixing treatment bath described later. In the dry stretching method, the PVA film after absorbing water can be uniaxially stretched under the atmosphere. Among these, the stretching treatment is preferably a wet stretching method, and more preferably a wet stretching method in which uniaxial stretching is performed in an aqueous solution containing boric acid. The boric acid concentration in the boric acid aqueous solution is preferably in the range of 0.5 to 6.0 mass%, more preferably in the range of 1.0 to 5.0 mass%, and particularly preferably in the range of 1.5 to 4.0 mass%.
[0094] The stretching temperature in the stretching treatment is preferably in the range of 45 to 60°C.
[0095] In addition, from the perspective of polarization performance, the stretching ratio in the stretching treatment is preferably 4 times or more, more preferably 4.5 times or more, and particularly preferably 5 times or more. The upper limit of the stretching ratio is not particularly limited, and the stretching ratio is preferably 8 times or less, and can be 5.5 times or less.
[0096] In the manufacture of the polarizing film, the PVA film can be appropriately cleaned (cleaning treatment) between the above-mentioned steps. From the perspective of being able to more firmly adsorb the dichroic pigment to the PVA film, it is preferred to perform the cleaning treatment before the drying step described later. As a cleaning bath used in cleaning, an aqueous solution containing one or more boron compounds such as boric acid and borax can be used. In addition, iodine compounds, metal compounds, etc. can be added to the cleaning bath as needed. At this time, the concentration of the boron compound in the cleaning bath is preferably 1 to 15% by mass. In the case where potassium iodide is contained in the above-mentioned aqueous solution, its concentration is preferably 0.01 to 10% by mass. The temperature of the cleaning bath is preferably 15 to 60°C, and particularly preferably 20 to 40°C.
[0097] The method for producing the polarizing film is not necessarily limited, but for reasons described below, the stretched polarizing film is preferably dried by heating in the drying step. The drying is preferably performed at 30 to 150°C, particularly preferably at 50 to 130°C.
[0098] In the method for producing a polarizing film, one of the above steps may be performed a plurality of times. In addition, a plurality of treatments may be performed simultaneously in one step.
[0099] [Polarizing plate]
[0100] The polarizing plate of the present invention can be obtained by, for example, pasting a protective film on both sides or one side of the above-mentioned polarizing film. The polarizing plate, for example, includes the above-mentioned polarizing film and a protective film, and the protective film is laminated on both sides or one side of the above-mentioned polarizing film directly or with the aid of an adhesive or a bonding agent. The polarizing plate of the present invention can take into account both polarization performance and thermoformability by including the above-mentioned polarizing film. As the protective film, optically transparent and mechanically strong protective films can be listed, specifically, for example, cellulose triacetate (TAC) film, cellulose acetate-butyrate (CAB) film, acrylic film, polyester film, cyclic olefin (COP) film, etc. can be used. In addition, as adhesives for pasting, PVA-based adhesives, urethane-based adhesives, ultraviolet curing adhesives, etc. can be listed. Furthermore, for pasting, adhesives can also be used. As adhesives, representatively, acrylic adhesives can be used.
[0101] The polarization degree of the polarizing plate of the present invention is preferably 80% or more. By making the polarization degree 80% or more, the light shielding function of the thermoformed body and the effect of preventing reflection are fully exerted. The polarization degree of the polarizing plate is more preferably 85% or more, and particularly preferably 90% or more. In addition, the upper limit of the polarization degree is not particularly limited, but from the aspect of being able to further suppress the generation of cracks when manufacturing the thermoformed body, it is preferably 99.7%, more preferably 99.5%, and particularly preferably 99.3%.
[0102] The monomer transmittance of the polarizing plate of the present invention is not particularly limited. For sunglasses, when the monomer transmittance of the polarizing plate is less than 20%, the field of view may become too dark and the safety may be reduced. In addition, in vehicle-mounted applications, when the monomer transmittance of the polarizing plate is less than 20%, the color tone of the instrument panel becomes darker, and it is difficult to observe the decorative color of the instrument panel, so it is possible to damage the design. For these reasons, the monomer transmittance of the polarizing plate is preferably 20% or more, and more preferably 25% or more. On the other hand, the upper limit of the monomer transmittance of the polarizing plate is not particularly limited. From the perspective of being able to exert more sufficient polarization performance, the monomer transmittance of the polarizing plate is preferably 38% or less, and more preferably 35% or less. It should be noted that the method for measuring the polarization degree and monomer transmittance of the polarizing plate is as follows. Take a rectangular film with a length direction of 3cm and a width direction of 1.5cm from the central part of the width direction of the polarizing plate. Use a spectrophotometer with an integrating sphere ("V7100" manufactured by Japan SCOP Corporation) to measure the polarization degree and monomer transmittance of the film at the maximum absorption wavelength in the visible light region.
[0103] The method of attaching the protective film to both sides or one side of the polarizing film is not particularly limited, and the protective film can be attached by any optional and known method. For example, from the perspective of production efficiency, a method of continuously attaching the protective film to the polarizing film is preferred.
[0104] The polarizing plate obtained in this way has sufficient polarization performance and has the property that cracks are not easily generated even when thermoformed. Therefore, the polarizing plate can be suitably used as a polarizing plate in the shape of sunglasses or instrument panels.
[0105] The crack rate when a thermoformed body is formed using the polarizing plate of the present invention is not particularly limited. The crack rate is preferably 0 to 40% when a mold having a spherical concave with a curvature radius of 5.2 cm and a depth of 3.5 cm is used, and the temperature of the polarizing plate is 107° C. and the vacuum degree is 0.01 MPa. When the crack rate measured under the above conditions is 40% or less, it can be judged that cracks are not easily generated even when performing heat vacuum forming with a large deformation amount. The crack rate is more preferably 0 to 30%, and particularly preferably 0 to 20%.
[0106] [Thermoformed body]
[0107] The thermoformed product of the present invention can be obtained by thermoforming the above-mentioned polarizing plate.
[0108] The maximum elongation of the thermoformed body of the present invention is not particularly limited, but is preferably 35% or less, and more preferably 30% or less. By setting the maximum elongation of the thermoformed body to 35% or less, the decrease in the polarization degree of the thermoformed body caused by deformation in a direction perpendicular to the stretching direction is suppressed, and a more sufficient polarization performance can be exerted. Here, the maximum elongation of the thermoformed body refers to the elongation of the deformed length after molding (maximum deformation length) at the position (cutting surface) where the deformation length of the cut surface (length of the periphery) reaches the maximum when the thermoformed body is cut using a plane perpendicular to the plane of the polarizing film (polarizing plate) before thermoforming, relative to the length before thermoforming. The above-mentioned length before thermoforming can adopt the diameter of the molding mold used. For example, as Fig. 9 As shown, the length before hot forming is the diameter B of the forming die, and the maximum deformation length A corresponding to the diameter B of the forming die is the length along the inner surface of the forming die in the cross section.
[0109] The polarization degree of the thermoformed article of the present invention is not particularly limited. From the perspective of being able to exert sufficient polarization performance and suppressing the reduction of the light-shielding function, the polarization degree of the thermoformed article is preferably 80% or more, more preferably 86% or more, and particularly preferably 91% or more. In addition, the upper limit of the polarization degree of the thermoformed article is not particularly limited. If the polarization degree is too high, the color tone of the instrument panel may become dark. Therefore, the polarization degree of the thermoformed article is preferably 99.7% or less, more preferably 99.5% or less, and particularly preferably 99.3% or less. The polarization degree of the thermoformed article can be 96% or less.
[0110] The monomer transmittance of the thermoformed body of the present invention is not particularly limited. For sunglasses, when the monomer transmittance of the thermoformed body is less than 20%, the field of view may become dark and the safety may become low. In addition, in vehicle-mounted applications, when the monomer transmittance of the thermoformed body is less than 20%, the color tone of the instrument panel becomes darker and the decorative color of the instrument panel is difficult to see, so the design may be impaired. For these reasons, the monomer transmittance of the thermoformed body is preferably 20% or more, more preferably 25% or more. On the other hand, the upper limit of the monomer transmittance of the thermoformed body is not particularly limited. From the perspective of being able to exert more sufficient polarization performance, the monomer transmittance of the thermoformed body is preferably 40% or less, more preferably 35% or less, and particularly preferably 30% or less. It should be noted that the method for measuring the polarization degree and monomer transmittance of the thermoformed body is as described below.
[0111] The thickness of the thinnest part of the thermoformed body of the present invention is not particularly limited, and is preferably 1 to 200 μm. When the thickness is less than 1 μm, the handling property may be low and continuous production may not be possible. Therefore, the thickness is more preferably 3 μm or more. On the other hand, when the thickness exceeds 200 μm, the shrinkage of the thermoformed body may be significantly increased. The thickness is more preferably 180 μm or less.
[0112] [Method for producing thermoformed article]
[0113] The method for producing the thermoformed article of the present invention is not particularly limited, but the thermoformed article of the present invention can be efficiently produced by adopting the following method for producing the thermoformed article.
[0114] In the method for manufacturing a thermoformed body of the present invention, the thermoforming method is not limited, and the above-mentioned polarizing plate can be thermoformed to obtain a thermoformed body by, for example, heated vacuum forming, heated pressure forming, heated pressurized forming, etc. The heating temperature is not particularly limited. If the temperature is too high, the polarizing plate melts. Therefore, the temperature of the polarizing plate is preferably below 200°C, more preferably below 160°C, and particularly preferably below 110°C. On the other hand, the lower limit of the heating temperature is preferably above the glass transition temperature of PVA and the protective film. Therefore, the temperature of the polarizing plate is preferably above 80°C, more preferably above 90°C, and particularly preferably above 105°C. The vacuum degree is not particularly limited. From the perspective of being able to fully form, it is preferably above 0.001MPa. In addition, the upper limit of the vacuum degree is not particularly limited. From the perspective of being able to obtain a beautiful molded body, the vacuum degree is preferably less than 0.1MPa.
[0115] The method for producing a thermoformed article may be a method for producing a polarizing plate that has undergone a drying step of heating and drying in the production process of a polarizing film or a polarizing plate. By thermoforming the polarizing plate that has undergone the drying step, it is possible to suppress the poor durability and time-dependent changes in the shape of the thermoformed article caused by excessive moisture. In addition, when drying is performed before thermoforming, it is possible to suppress shrinkage and cracking of the thermoformed article during drying, and to suppress changes in the shape of the thermoformed article.
[0116] By using the polarizing plate of the present invention, a thermoformed body having sufficient polarization performance and few cracks even with a large deformation amount can be obtained. The thermoformed body can be applied to polarizing plates in the shape of sunglasses or instrument panels with high design.
[0117] Example
[0118] Hereinafter, the present invention will be specifically described by way of Examples, but the present invention is not limited to these Examples at all.
[0119] In addition, each evaluation method used in the following Examples and Comparative Examples is as follows.
[0120] [Calculation of crystallinity of PVA film]
[0121] (Wide-angle X-ray Diffraction (WAXD) Measurement of PVA Film)
[0122] Wide Angle X-ray Diffraction (WAXD) measurement was performed using D8 Discover manufactured by Bruker AXS. The incident X-ray wavelength was set to 0.154 nm (Cu target). The detector used was a VANTEC-500, a rare gas-enclosed micro-gap position-sensitive two-dimensional detector, and the camera distance (the distance between the sample and the detector) was set to about 170 mm. The filament current of the X-ray generator was set to 1 mA, the voltage was set to 50 kV, and a device with a collimator diameter of 0.5 mm was used.
[0123] Cut the PVA film into a rectangle with a short side of 5 mm and a long side of 20 mm. At this time, make the long side direction consistent with the length direction of the PVA film. Overlap the cut pieces of PVA film and stick them to the sample holder. Confirm in advance that the signal of the PVA film is sufficiently strong compared with the background scattering, the electrical noise of the detector, etc.
[0124] The sample holder was mounted on the stage of the X-ray device in such a way that the length direction of the PVA film was aligned with the X-axis direction of the D8 Discover. At this time, the normal line relative to the surface of the PVA film was aligned with the incident direction of the X-ray. The X-axis, Y-axis, and Z-axis of the device were adjusted in such a way that the X-ray was irradiated toward the PVA film from the aforementioned incident direction.
[0125] The WAXD measurement is carried out under the following conditions. The ω axis of the sample (an axis set so that the angle between the normal line relative to the surface of the PVA film and the incident direction of the X-ray is ω. It is usually referred to as the θ axis.) is set to 11°, the 2θ axis (an axis set so that the angle between the normal line relative to the surface of the detector and the incident direction of the X-ray is 2θ) as the detector position is set to 22°, and the ψ axis corresponding to the rotation within the surface of the PVA film is set to 90° or 0°. The ψ axis is consistent with the azimuthal direction within the surface of the PVA film. When the stretching direction of the PVA film is set to the meridian direction and the in-plane and perpendicular direction is set to the equatorial direction, if the ψ axis is 90°, the diffraction information in the equatorial direction can be obtained, and if the ψ axis is 0°, the diffraction information in the meridian direction can be obtained. The diffraction or scattering observed by the detector satisfies Bragg's condition. Under this measurement condition, for example, the signal from the 110 diffraction of the detected PVA crystal is based on the diffraction of the (110) plane that is roughly consistent with the thickness direction of the PVA film. The ψ axis is set to 90° or 0°, and the X-ray exposure time is set to 10 minutes for each measurement.
[0126] (WAXD measurement data analysis of PVA film)
[0127] The acquired two-dimensional WAXD images were converted into one-dimensional curves of X-ray intensity I (2θ) relative to 2θ using DIFFRAC.EVA software. The 2θ range was set to 5° to 38°, and the ψ axis range was set to -135 to -45°. The sampling step was set to 0.02° intervals. The same operation was also applied to the background scattering data (data measured without PVA film installed and under the same conditions).
[0128] The analysis of the I(2θ) curve is performed according to the following steps. First, the I(2θ) curve obtained by the film measurement is subtracted from the I(2θ) curve obtained by the background measurement. Figure 1 In this way, a baseline straight line is created that connects the intensity value I(15) when the 2θ position is 15° and the intensity value I(25) when the 2θ position is 25°, and is further subtracted from the I(2θ) curve after subtracting the background scattering ( Figure 2 ). The baseline line is a linear function that passes through the two points (15, I(15)) and (25, I(25)) on the I(2θ)-2θ coordinates.
[0129] For the baseline corrected I(2θ) curve data ( Figure 2 ), and the PVA amorphous peak was fitted using the following Gaussian function.
[0130] f(x) = a·exp(-{(xb) / c} 2 )
[0131] Here, a: peak height, b: peak top position, and c: half value width.
[0132] Furthermore, at this time, the least square method is used to fit the deviations of 2θ=15° to 17.6° and 21° to 21.6° to be the smallest. In addition, the peak position 2θ of the Gaussian function at this time becomes the (110) plane, in other words, it becomes near 20° ( Figure 3 ). The peak area of the fitting function is defined as the amorphous amount (A).
[0133] Similarly, for the baseline-corrected I(2θ) curve data ( Figure 2 ) were fitted using the same function as above. At this time, the peak top appeared near 20° for the (110) plane and near 23° for the (200) plane. Furthermore, the least squares method was used to fit the peaks in the (110) plane and (200) plane, including the previously obtained Gaussian function of the amorphous PVA, in such a way that the difference between the sum of all Gaussian functions and the baseline-corrected data was minimized ( Figure 4 ). The peak areas of these Gaussian functions are set as the crystallization amount (B) and (C), respectively. That is, the peak area of the fitting function of the peak in the (110) plane is set as the crystallization amount (B), and the peak area of the fitting function of the peak in the (200) plane is set as the crystallization amount (C).
[0134] The value obtained from the area values of the amorphous and crystalline regions ((A), (B), and (C)) by the following formula is defined as the crystallinity.
[0135] Crystallinity (%) = {(B) + (C)} / {(A) + (B) + (C)} × 100
[0136] [Calculation of the amount of highly oriented amorphous and highly oriented PVA-boric acid aggregated structures in polarizing films]
[0137] (Wide Angle X-ray Diffraction (WAXD) Measurement of Polarizing Film)
[0138] Wide Angle X-ray Diffraction (WAXD) measurement was performed using D8 Discover manufactured by Bruker AXS. The incident X-ray wavelength was set to 0.154 nm (Cu target). The detector used was VANTEC-500, a rare gas-enclosed micro-gap position-sensitive two-dimensional detector, and the camera distance (the distance between the sample and the detector) was set to about 100 mm. The filament current of the X-ray generator was set to 1 mA, the voltage was set to 50 kV, and a device with a collimator diameter of 0.5 mm was used.
[0139] Cut the polarizing film into a rectangle with a short side of 5 mm and a long side of 20 mm. At this time, make the long side direction consistent with the stretching direction of the polarizing film. Overlap the cut polarizing films and fix them to the sample holder. At this time, the polarizing films must be fixed in such a way that the stretching directions of each polarizing film are completely consistent. Confirm in advance that the signal of the polarizing film is sufficiently strong compared with the background scattering, the electrical noise of the detector, etc.
[0140] The sample holder was mounted on the stage of the X-ray device in such a way that the stretching direction of the polarizing film was aligned with the X-axis direction of the D8 Discover. At this time, the normal line relative to the surface of the polarizing film was aligned with the incident direction of the X-ray. The X-axis, Y-axis, and Z-axis of the device were adjusted in such a way that the X-ray was irradiated toward the polarizing film from the aforementioned incident direction.
[0141] The WAXD measurement is carried out using the following conditions. The ω axis (an axis set so that the angle between the normal line relative to the surface of the polarizing film and the incident direction of the X-ray is ω. It is usually referred to as the θ axis) of the sample is set to 11°, the 2θ axis (an axis set so that the angle between the normal line relative to the surface of the detector and the incident direction of the X-ray is 2θ) as the detector position is set to 22°, and the ψ axis corresponding to the rotation within the plane of the polarizing film is set to 50°. The ψ axis is consistent with the azimuthal direction within the plane of the polarizing film. The diffraction or scattering observed by the detector satisfies Bragg's condition. Under this measurement condition, for example, the signal from the 110 diffraction of the detected PVA crystal is based on the diffraction of the (110) plane that is roughly consistent with the thickness direction of the polarizing film. The X-ray exposure time is set to 30 minutes for measurement.
[0142] (WAXD measurement data analysis of polarizing films)
[0143] The obtained two-dimensional WAXD photograph was converted into a one-dimensional curve of X-ray intensity I (2θ) relative to 2θ using DIFFRAC.EVA software. The 2θ range was set to 5° to 35°, and the stretching direction was set to 0°, and the I (2θ) curves segmented in the azimuth range of -5° to 5°, 5° to 15°, 15° to 25°, 25° to 35°, 35° to 45°, 45° to 55°, 55° to 65°, 65° to 75°, 70° to 80°, 75° to 85°, 80° to 90°, 85° to 95°, 90° to 100°, 95° to 105°, 100° to 110°, and 105° to 115° were obtained. The sampling step was set to 0.05° intervals. The same operation was also applied to the background scattering data (data measured under the same conditions without installing a polarizing film).
[0144] The analysis of the I(2θ) curve is performed according to the following steps. First, the I(2θ) curve obtained by measuring the polarizing film is subtracted from the I(2θ) curve obtained by measuring the background scattering in the same azimuth range. Figure 5 In this way, a baseline straight line is created that connects the intensity value I(6.5) when the 2θ position is 6.5° and the intensity value I(30.5) when the 2θ position is 30.5°, and is further subtracted from the I(2θ) curve after background scattering is subtracted. The baseline straight line is a linear function that passes through the two points (6.5, I(6.5)) and (30.5, I(30.5)) on the I(2θ)-2θ coordinate.
[0145] Figure 6 The I(2θ) curve after baseline correction is shown in . For 2θ, the broad and loose scattering components observed in the range of 10° to 30° are mainly generated by the amorphous PVA. For 2θ, the peak components observed in the range of 19° to 21° are generated by the diffraction based on the (1-10) plane and the (110) plane of the PVA crystal. On the other hand, it is known that: for 2θ, the peak components observed in the range of 21° to 23° appear when boric acid is added to PVA, and it can be considered that it is a diffraction signal from the structure formed by the interaction between PVA and boric acid. The structure formed by the interaction between PVA and boric acid is called "PVA-boric acid aggregate structure". That is, the corrected I(2θ) curve obtained by measuring the polarizing film can be separated into three components: "PVA amorphous", "PVA crystalline" and "PVA-boric acid aggregate structure". Here, waveform separation analysis is applied to the corrected I(2θ) curve.
[0146] It is assumed that the scattering or diffraction signals from "PVA amorphous", "PVA crystalline" and "PVA-boric acid aggregate structure" can be represented by Gaussian functions. They are set as Gaussian function A, Gaussian function B and Gaussian function C respectively. The parameters defining the shape of the Gaussian function are set as the peak position x, peak height h and peak width (here refers to the standard deviation σ of the normal distribution). In such a way that the calculated-I (2θ) curve, which is the sum of the three Gaussian functions representing each component, is consistent with the corrected I (2θ) curve, the peak position x, peak height h and peak width of the three Gaussian functions are set as variable parameters, and all parameters are optimized using least squares fitting. The results are shown in Figure 6 In this waveform separation analysis, the calculated-I(2θ) curve must be properly expressed using three Gaussian functions in a manner that reflects the structure of the polarizing film without being affected by the deviation of the measured data or the error caused by the analysis or the systematic error of the fitting. Here, in this experiment, the following constraints (a) to (f) are introduced into the waveform separation analysis for implementation.
[0147] (a) For 2θ, the signals in the ranges of 13° to 16° and 25° to 28° are regarded as scattering caused by “PVA amorphous”, and therefore, only Gaussian function A is used to reproduce the corrected I(2θ) curve in the same 2θ range.
[0148] (b) For 2θ, the signal in the range of about 17° to 21° is the scattering and diffraction generated by "PVA amorphous" and "PVA crystalline", and the contribution of "PVA crystalline" is particularly large. The position of the diffraction peak based on the crystal is known, and here, the peak position x of the Gaussian function B is fixed.
[0149] (c) For 2θ, the signal in the range of about 20° to 23° is the scattering and diffraction generated by "PVA amorphous" and "PVA-boric acid aggregate structure". In particular, the contribution of "PVA-boric acid aggregate structure" is large. Here, the peak position x of the Gaussian function C is fixed.
[0150] (d) In order to properly separate "PVA crystals" from "PVA-boric acid aggregate structure", the peak widths of Gaussian function B and Gaussian function C are set to the same value. This is because the diffraction intensities within 17° to 21° and 20° to 23° are roughly the same regardless of the polarizing film measured, and it can be estimated that there is no significant difference in the shape of the diffraction peak based on "PVA crystals" and the diffraction peak based on "PVA-boric acid aggregate structure".
[0151] (e) In view of the above (a) to (d), the optimal values of the peak top position x and peak width σ of each of the three Gaussian functions are explored so that the calculated-I(2θ) curve, which is the sum of the three Gaussian functions, can well reproduce all the corrected I(2θ) curves.
[0152] (f) For all corrected I(2θ) curves, only the peak heights h of the three Gaussian functions were set as variable parameters and least squares fitting was performed. The fitting range was set to 6.5° to 30.5°.
[0153] It should be noted that in the equatorial direction, that is, in the I (2θ) curve at an azimuth angle of 90°, a 100° diffraction peak based on PVA crystals oriented along the stretching direction was observed at the 2θ position and about 11°. When the 100° diffraction peak was observed, it was shown that the diffraction peak shape can be represented by a Gaussian function, which is included in the waveform separation analysis performed on the I (2θ) curve. That is, the peak top position x, peak height h and peak width σ of the Gaussian function are appropriately adjusted, and the least squares fitting is performed.
[0154] After the least squares fitting, the areas of the three Gaussian functions are calculated and regarded as the integrated intensity values (A) of the signals generated by "PVA amorphous", "PVA crystalline" and "PVA-boric acid aggregate structure", respectively. When the 100 diffraction peak is observed, the integrated intensity value of the 100 diffraction peak is included in the "PVA crystalline". The above-mentioned waveform separation analysis is performed on the corrected I (2θ) curves of all azimuths to calculate the integrated intensity values (A) of "PVA amorphous", "PVA crystalline" and "PVA-boric acid aggregate structure". It should be noted that these analyses can be performed using Excel software manufactured by Microsoft.
[0155] The graph obtained by plotting the integrated intensity values (A) of "PVA amorphous", "PVA crystalline" and "PVA-boric acid aggregate structure" obtained by waveform separation analysis with respect to the azimuth angle is Figure 7 Here, the azimuth angle is defined as follows. For example, the analysis results of the corrected I(2θ) curve in the azimuth angle range of -5° to 5° are plotted relative to the azimuth angle of 0°, and the analysis results of the corrected I(2θ) curve in the azimuth angle range of 85° to 95° are plotted relative to the azimuth angle of 90°.
[0156] Azimuthal dispersion plot of the integrated intensity values of each component It reflects the orientation state of each component relative to the stretching direction of the polarizing film. When the scattered or diffracted signals observed in the analyzed 2θ range are regarded as mainly derived from the interference between the PVA molecular chains, the proportion of the signal observed at an azimuth angle of 90° is roughly equal to the proportion of the components of the PVA molecular chains arranged along the stretching direction. The proportion of the signal observed at an azimuth angle of 0° is roughly equal to the proportion of the components of the PVA molecular chains arranged in a direction perpendicular to the stretching direction. That is, Figure 7 Roughly equal to the distribution function of the orientation state of each component When PVA is completely in a non-oriented state, there is no azimuthal dependence of the distribution function. On the other hand, if PVA is oriented with distribution in the stretching direction, the distribution function shows a peak shape with 90° as the maximum intensity.
[0157] Here, the azimuthal dispersion of the integrated intensity values is plotted Distribution function separated into orientation components and the distribution function of the non-oriented component The distribution function of the non-oriented component has no azimuthal dependence, so it is set to (C is a constant). Figure 8 As shown in the figure, the component of C that becomes a constant regardless of the azimuth is The component with probability distribution at a specific azimuth is It can be seen that in order to plot the azimuth dispersion with good accuracy for any polarizing film get The data can be processed as follows: Assume that the distribution functions of the orientation components of "PVA crystal" and "PVA-boric acid aggregate structure" are It can be expressed by the Lorentz function, with the peak top position set to 90° and the peak height h and the peak half-value width set as variable parameters. Assuming that the distribution function of the orientation component of "PVA amorphous" is It can be expressed as the linear sum of two Gaussian functions, with the peak position set to 90° and the peak height h and half-value width of each function set as variable parameters. and The sum is well reproduced The least squares fitting method is used to obtain the optimal solution of constant C, peak height h, and peak half-value width. The fitting is implemented in the azimuth range of 0° to 110°. It should be noted that the orientation state of the polarizing film can be considered to be symmetrical based on the stretching direction. Therefore, in the calculation of the following integral value, the obtained distribution function and It is applied within the azimuth range of 0° to 180°.
[0158] Here, the distribution function of the orientation component obtained by the above fitting is Among them, the azimuth The ratio of the high orientation component in the range of 80° to 100° is calculated as follows. First, the distribution function of the orientation component in the azimuth angle range of 0° to 180° is calculated: The integral value of . Set it as F1. Next, calculate the distribution function of the orientation component Azimuth The integral value of the range of 80° to 100° is defined as F1a. F1-F1a is the integral value of 0° to 80° and 100° to 180°, which is defined as F1b. F1b is the orientation component with a small orientation degree. In the azimuth range of 0° to 180°, the distribution function of the non-oriented component is calculated. The integral value F2. For "PVA amorphous", "PVA crystalline" and "PVA-boric acid aggregate structure", the values of F1a, F1b and F2 are obtained respectively. F1a is the amount proportional to the high orientation component, F1b is the amount proportional to the low orientation component, and F2 is the amount proportional to the non-oriented component.
[0159] The existence ratio of the high-oriented component, low-oriented component and non-oriented component of each of "PVA amorphous", "PVA crystalline" and "PVA-boric acid aggregate structure", that is, the 9 components, is shown as the ratio of each component to the sum of the integral values of each component. They are set as F1a-PVA amorphous, F1b-PVA amorphous, F2-PVA amorphous, F1a-PVA crystalline, F1b-PVA crystalline, F2-PVA crystalline, F1a-PVA-boric acid aggregate structure, F1b-PVA-boric acid aggregate structure, and F2-PVA-boric acid aggregate structure.
[0160] Among them, the high orientation component of "PVA amorphous", namely F1a-PVA amorphous, is the aforementioned high orientation amorphous, and the ratio of this component to the sum of the 9 components is set as the "high orientation amorphous amount". In addition, the high orientation component F1a-PVA-boric acid aggregate structure of "PVA-boric acid aggregate structure" is the aforementioned high orientation PVA-boric acid aggregate structure, and the ratio of this component to the sum of the 9 components is set as the "high orientation PVA-boric acid aggregate structure amount".
[0161] [Calculation of Boric Acid Content (Mass %) in Polarizing Film]
[0162] After the polarizing film obtained in each embodiment or comparative example is humidified at a temperature of 23°C and a humidity of 50% RH for 16 hours, a sample of about 1 mg is taken and its mass (J (g)) is measured. Next, the sample is dissolved in 20 mL of distilled water to prepare an aqueous solution. The aqueous solution is used as a measurement sample, and its mass (K (g)) is measured. Thereafter, the boron concentration (L (ppm)) of the measurement sample is measured using a multifunctional ICP emission analyzer (ICPE-9000) manufactured by Shimadzu Corporation. Thereafter, the value calculated by substituting the numerical value into the following calculation formula is set as the boric acid content (mass %) in the polarizing film.
[0163] Boric acid content in polarizing film (mass %) = [(L × 10 -6 ×K) / J]×100 / (10.8 / 61.8)
[0164] [Evaluation of Maximum Elongation of Thermoformed Article]
[0165] When the deformation length (maximum deformation length) when the thermoformed body is cut using a surface perpendicular to the film surface before thermoforming so that the deformation length (peripheral length) of the cut surface becomes the maximum is defined as A, and the diameter of the molding die having a spherical concave shape used in thermoforming (i.e., the length before thermoforming) is defined as B, the elongation of A relative to B is defined as the maximum elongation (%) ( Fig. 9 ).
[0166] Maximum elongation (%) = ((AB) / B) × 100
[0167] [Evaluation of crack rate]
[0168] For the polarizing plates obtained in each embodiment or comparative example, a mold having a spherical concave with a curvature radius of 5.2 cm and a depth of 3.5 cm was used, and when the temperature of the polarizing plate was 107° C. and the vacuum degree was 0.01 MPa, the ratio of the number of samples having one or more cracks among the total number of samples was calculated. The number of samples was set to 6.
[0169] Crack rate (%) = (number of samples with cracks / total number of samples) × 100
[0170] [Evaluation of polarization performance of thermoformed articles]
[0171] A rectangular film having a length direction of 3 cm and a width direction of 1.5 cm was taken from the thinnest part of the thermoformed body obtained in each embodiment or comparative example before thermoforming of the polarizing plate. The polarization degree and single transmittance of the film at the maximum absorption wavelength in the visible light region were measured using a spectrophotometer with an integrating sphere ("V7100" manufactured by JASCO Corporation).
[0172] [Example 1]
[0173] A film-making stock solution containing 100 parts by mass of PVA (polymerization degree of 2,300, saponification degree of 99.3 mol%), 0 parts by mass of glycerol as a plasticizer, and 0.1 parts by mass of sodium polyoxyethylene lauryl ether sulfate as a surfactant, and water as a liquid solvent with a volatility of 66% by mass, was used to continuously form a long PVA film with a thickness of 80 μm using a film-making device having 18 drying rollers whose rotating axes are parallel to each other. When the crystallinity of the obtained PVA film was calculated using the above method, it was 33%.
[0174] Specifically, the above-mentioned film-making stock solution is sprayed from a T-shaped slit die in a film shape onto a first drying roller (surface temperature of 95°C, peripheral speed of 10.6 m / min), and on the first drying roller, hot air (temperature of 90°C, dew point temperature of 10°C) is evenly blown to the entire non-contact surface of the first drying roller at a wind speed of 5 m / sec, while drying until the volatile fraction of the polyvinyl alcohol film reaches 25% by mass. Then, it is peeled off from the first drying roller (the volatile fraction when peeled off from the first drying roller is 25% by mass), and the first drying roller contact surface and the first drying roller non-contact surface of the PVA film are alternately opposite to each drying roller, and dried by the second drying roller and the subsequent drying rollers (surface temperature of 75-95°C, peripheral speed of 10.6 m / min), and then, after cutting and removing the two end portions (edges) in the width direction, it is rolled into a roll to obtain the above-mentioned PVA film.
[0175] A sample of 40 cm in width and 15 cm in length was cut from the central part of the width direction of the obtained PVA film in such a manner that uniaxial stretching could be performed in the range of 40 cm in width and 10 cm in length. The sample was immersed in water at a liquid temperature of 32° C. for 2 minutes and uniaxially stretched in the longitudinal direction to 2.0 times of the original length (first stage stretching) to swell (swelling treatment). Next, the sample was immersed in a direct blue 15 solution (dyeing bath: the concentration of direct blue 15 as a dichroic organic dye was 0.013 mass %, the concentration of sodium sulfate was 0.42 mass %, and the concentration of sodium tripolyphosphate was 0.42 mass %) at a liquid temperature of 32° C. for 5 minutes, and dyed (dyeing treatment) while uniaxially stretching in the longitudinal direction to 1.3 times (2.5 times as a whole) (second stage stretching). Next, during the period of immersion in a boric acid aqueous solution (cross-linking bath: boric acid concentration of 2.6 mass %) at a liquid temperature of 32°C for 1 minute, cross-linking was performed while uniaxially stretching to 1.2 times (3.0 times as a whole) in the length direction (third stage stretching). Next, during the period of immersion in a boric acid aqueous solution (stretching bath: boric acid concentration of 2.8 mass %) at a liquid temperature of 57°C, uniaxially stretching to 1.7 times (5.0 times as a whole) in the length direction (fourth stage stretching) (stretching treatment). Next, it was immersed in a boric acid aqueous solution (cleaning bath: boric acid concentration of 1.5 mass %) at a liquid temperature of 22°C for 1 second without stretching and cleaned (cleaning treatment). Next, in order to prevent dimensional changes in the length direction, the two ends were fixed and dried in a dryer at 60°C for 3 minutes (drying treatment) to obtain a polarizing film. The thickness of the obtained polarizing film was measured, and the highly oriented amorphous amount, the highly oriented PVA-boric acid aggregated structure amount and the boric acid content were measured using the above method. The results are shown in Table 1. The obtained polarizing film contained no halide.
[0176] The central portion in the width direction of the obtained polarizing film was cut into a size of 25 cm wide by 25 cm long, and acrylic films (manufactured by Kuraray, HI5000, thickness 75 μm) were adhered to both sides using an adhesive (manufactured by Meiguan Imaging, MPD62, thickness 25 μm) to prepare a polarizing plate of 25 cm wide by 25 cm long.
[0177] For the obtained polarizing plate, a heater set at 250°C was used on a vacuum pressure forming machine (FVT-400) manufactured by Ribizaka Engineering Co., Ltd. to heat the polarizing plate to 107°C, and then a mold having a spherical depression with a radius of curvature of 5.2 cm and a depth of 3.5 cm was used to perform heating vacuum forming for 10 seconds at a vacuum degree of 0.01 MPa to produce a thermoformed body with a maximum elongation of 30%. After cooling for 5 seconds while the thermoformed body was held in a fixture, it was removed from the fixture to obtain a thermoformed body. For the obtained thermoformed body, the crack rate, polarization degree and monomer transmittance were calculated using the above method. The crack rate and polarization degree are shown in Table 1. In addition, the monomer transmittance is 32%.
[0178] [Example 2]
[0179] During the stretching process, the temperature of the boric acid aqueous solution was changed to 49°C. Except for this, the same operation as in Example 1 was performed to manufacture a PVA film, a polarizing film, a polarizing plate, and a thermoformed body. The thickness of the obtained polarizing film was measured, and the amount of highly oriented amorphous, the amount of highly oriented PVA-boric acid aggregated structure, and the boric acid content were measured by the above method. The results are shown in Table 1. Furthermore, for the obtained thermoformed body, the crack rate, polarization degree, and monomer transmittance were calculated by the above method. The crack rate and polarization degree are shown in Table 1. In addition, the monomer transmittance was 31%.
[0180] [Example 3]
[0181] The amount of glycerol in the film-making stock solution was changed to 12 parts by mass, and the thickness of the prepared PVA film was changed to 75 μm. The same operation as in Example 2 was performed to manufacture PVA films, polarizing films, polarizing plates and thermoformed bodies. When the crystallinity of the obtained PVA film was calculated by the above method, it was 34%. The thickness of the obtained polarizing film was measured, and the amount of highly oriented amorphous, the amount of highly oriented PVA-boric acid aggregated structure and the boric acid content were measured by the above method. The results are shown in Table 1. Furthermore, for the obtained thermoformed body, the crack rate, polarization degree and monomer transmittance were calculated by the above method. The crack rate and polarization degree are shown in Table 1. In addition, the monomer transmittance is 31%.
[0182] [Comparative Example 1]
[0183] During the stretching process, the ratio was changed to 2.2 times (6.0 times as a whole). Other than that, the same operation as in Example 2 was performed to manufacture a PVA film, a polarizing film, a polarizing plate, and a thermoformed body. When the crystallinity of the obtained PVA film was calculated by the above method, it was 33%. The thickness of the obtained polarizing film was measured, and the amount of highly oriented amorphous, the amount of highly oriented PVA-boric acid aggregated structure, and the boric acid content were measured by the above method. The results are shown in Table 1. Furthermore, for the obtained thermoformed body, the crack rate, polarization degree, and monomer transmittance were calculated by the above method. The crack rate and polarization degree are shown in Table 1. In addition, the monomer transmittance is 33%.
[0184] [Comparative Example 2]
[0185] During the stretching process, the ratio was changed to 2.2 times (6.0 times as a whole). Other than that, the same operation as in Example 3 was performed to manufacture a PVA film, a polarizing film, a polarizing plate, and a thermoformed body. When the crystallinity of the obtained PVA film was calculated by the above method, it was 34%. The thickness of the obtained polarizing film was measured, and the amount of highly oriented amorphous, the amount of highly oriented PVA-boric acid aggregated structure, and the boric acid content were measured by the above method. The results are shown in Table 1. Furthermore, for the obtained thermoformed body, the crack rate, polarization degree, and monomer transmittance were calculated by the above method. The crack rate and polarization degree are shown in Table 1. In addition, the monomer transmittance is 31%.
[0186] [Table 1]
[0187]
[0188] As shown in Table 1, in Examples 1 to 3, although the maximum elongation was 30%, a thermoformed body with few cracks and sufficient polarization performance was obtained.
[0189] Description of Reference Numerals
[0190] 1. Maximum deformation length A
[0191] 2. Diameter B of the molding die
Claims
1. A polarizing plate comprising a polarizing film having polyvinyl alcohol as a main component, wherein the thickness of the polarizing film is greater than 20 μm, and the amount of highly oriented amorphous in the polarizing film is 10.0 to 18.0%.
2. The polarizing plate according to claim 1, wherein The polarizing film has a boric acid content of 5 to 30% by mass.
3. The polarizing plate according to claim 1, wherein The polarizing film has a highly oriented PVA-boric acid aggregated structure content of 4.3% or less.
4. The polarizing plate according to claim 1, wherein The polarizing film includes a dichroic organic dye.
5. The polarizing plate according to claim 1, wherein When heat vacuum forming was performed using a mold having a spherical concave with a curvature radius of 5.2 cm and a depth of 3.5 cm at a temperature of 107° C. and a vacuum degree of 0.01 MPa, the crack rate was 0 to 40%. 6 . A thermoformed product obtained by thermoforming the polarizing plate according to claim 1 .
7. The thermoformed article according to claim 6, which has a maximum elongation of 35% or less.
8. The thermoformed body according to claim 6, which has a polarization degree of 80 to 99.7%. 9 . A method for producing a thermoformed body, comprising the step of thermoforming the polarizing plate according to claim 1 at 105° C. to 110° C.
Citation Information
Patent Citations
Window reflection reduction mechanism for vehicles
JP2004130916A
Vehicle interior structure, interior member used for the same and method for manufacturing the same, and method for manufacturing polarization member
JP2019051874A
Polarizing film and method for producing same
WO2017138551A1
Polarizing film, polarizing plate, and method for producing said polarizing film
WO2020255779A1